Evaluasi Pembelajaran Pai Dalam Mengembangkan Kemampuan Siswa Di Sdn Karang Asih 07 Cikarang Utara - Selpi Dwi Ariani; Salwa Salsabila Putri Sulaiman; Rahma Nabiilah Nuraniyyah; Raihan Azzam Arrayan; Sobur Sobur; Shofiyana Nadia Fairuz (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2026)
This study was motivated by importance from evaluating Islamic education (PAI) learning in supporting That development of students’ abilities at the elementary school level. Learning evaluation is an essential part of the educational process because it functions to determine the level of students’ success in understanding learning materials as well as the development of their religious attitudes and skills. In PAI learning, evaluation does not only assess cognitive aspects but also includes affective and psychomotor aspects. However, the implementation of PAI learning evaluation in elementary schools still faces several challenges, such as limited learning time, differences in students’ abilities, difficulties in objectively assessing attitudes, and the lack of optimal use of technology in the evaluation process. This study aims to identify and analyze the implementation of PAI learning evaluation in developing students’ abilities at SDN Karang Asih 07 North Cikarang. This research used a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation involving PAI teachers and students as research subjects. The data were analyzed using the Miles and Huberman analysis technique through data reduction, data presentation, and conclusion drawing. The results showed that PAI learning evaluation was conducted through various forms of assessment, such as written tests, attitude observation, worship practices, assignments, and memorization of prayers and short surahs. These evaluations helped teachers identify students’ overall development in terms of knowledge, religious character building, and religious practice skills. This study also indicates that comprehensive learning evaluation can support the improvement of PAI learning quality in elementary schools. Therefore, teachers are expected to develop more innovative and authentic evaluation models to make the learning process more effective and suitable for students’ needs.